Secondary dislocations in type B and C injuries of the subaxial cervical spine: risk factors and treatment - Raisch, Philipp; Pflästerer, Jan; Kreinest, Michael; Vetter, Sven Y.; Grützner, Paul Alfred; Jung, Matthias (Journal of Clinical Medicine, 2024)
Introduction: This study analyzed the incidence of secondary dislocations (sDLs) after surgical stabilization of AO Spine type B and C injuries of the subaxial cervical spine (sCS). Materials and Methods: Patients treated for injuries of the sCS from 2010 to 2020 were retrospectively analyzed for the incidence of sDL within 60 days after first surgery. A univariate analysis of variables potentially influencing the risk of sDL was performed. Patients with solitary anterior stabilization underwent subgroup analysis. The treatment of sDLs was described. Results: A total of 275 patients were included. sDLs occurred in 4.0% of patients (n = 11) in the total sample, most frequently after solitary anterior stabilization with 8.0% (n = 10, p = 0.010). Only one sDL occurred after combined stabilization and no sDLs after posterior stabilization. In the total sample and the anterior subgroup, variables significantly associated with sDL were older age (p = 0.001) and concomitant unstable facet joint injury (p = 0.020). No neurological deterioration occurred due to sDL and most patients were treated with added posterior stabilization. sDL is frequent after solitary anterior stabilization and rare after posterior or combined stabilization. Discussion: Patients of higher age and with unstable facet joint injuries should be followed up diligently to detect sDLs in time. Neurological deterioration does not regularly occur due to sDL, and most patients can be treated with added posterior stabilization.
Gesehen am 24.05.2024